Enhanced Self‐Healing in Dual Network Entangled Hydrogels by Macromolecular Architecture and Alignment of Surface Functionalized hBN Nanosheets - Ratwani, Chirag R.; Donato, Katarzyna Z.; Grebenchuk, Sergey; Mija, Alice; Novoselov, Kostya S.; Abdelkader, Amr M. (Advanced materials interfaces, 2025)
Hydrogels have shown great promise as versatile biomaterials for various applications, ranging from tissue engineering to flexible electronics. Among their notable attributes, self‐healing capabilities stand out as a significant advantage, facilitating autonomous repair of mechanical damage and restoration of structural integrity. In this work, a dual network macromolecular biphasic composite is designed using an anisotropic structure which facilitates unidirectional chain diffusion and imparts superior self‐healing and mechanical properties. The resulting nanocomposite demonstrates significantly higher self‐healing efficiency (92%) compared to traditional polyvinyl alcohol (PVA) hydrogels, while also improving the tensile strength and elastic modulus, which typically compete with each other in soft materials. This improvement is attributed to enhanced barrier properties within the matrix due to the alignment of surface‐functionalized 2D hBN nanosheets along the biopolymer scaffold. The insights gained from this research can be leveraged to develop advanced self‐healing materials by using 2D nanofillers as “safety barriers” to define the movement of polymeric chains. This work presents a novel dual‐network hydrogel utilizing surface‐functionalized hBN nanosheets and directional freezing to create anisotropic channels. This alignment helps direct the polymer chain movement, achieving a 92% self‐healing efficiency and superior mechanical strength compared to conventional isotropic hydrogels.